1996
DOI: 10.1183/09031936.96.09091923
|View full text |Cite
|
Sign up to set email alerts
|

Weaning from mechanical ventilation

Abstract: W We ea an ni in ng g f fr ro om m m me ec ch ha an ni ic ca al l v ve en nt ti il la at ti io on n J. ManceboWeaning from mechanical ventilation. J. Mancebo. ERS Journals Ltd 1996. ABSTRACT: Weaning from mechanical ventilation is a period of transition from total ventilatory support to spontaneous breathing. It represents a relevant clinical problem because as many as 25% of intubated and mechanically-ventilated critically ill patients will need a progressive withdrawal from artificial ventilatory support.Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 83 publications
0
61
0
Order By: Relevance
“…Among the different ventilatory modes which can be used to wean neonates, PTV is a mode maintaining an inspiratory effort from the patient [13] and thus an exercise of respiratory muscles without excessive increase of V'O 2 as well as work of breathing. Thus, PTV seems to be an interesting ventilatory mode to wean infants with high OCB, as proposed in adults [2,14]. However, no clinical trial to date has confirmed this in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Among the different ventilatory modes which can be used to wean neonates, PTV is a mode maintaining an inspiratory effort from the patient [13] and thus an exercise of respiratory muscles without excessive increase of V'O 2 as well as work of breathing. Thus, PTV seems to be an interesting ventilatory mode to wean infants with high OCB, as proposed in adults [2,14]. However, no clinical trial to date has confirmed this in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…9,10) A previous study reported oral health problems in 70% of inpatients admitted to acute stage hospitals without full-time dental professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Weaning can be initiated if some conditions are reached. These conditions are: (i) improvement of the underlying disease; (ii) an adequate gas exchange; (iii) stable hemodynamics; (iv) adequate performance of the respiratory muscles with correct management of respiratory secretions; and (v) no major metabolic and/or electrolytic disturbances 9,10 . The correct management of respiratory secretions has to be evaluated because the patients need to protect their airway and clear the secretions with an effective cough.…”
Section: Weaning Processmentioning
confidence: 99%
“…This is the most common cause for weaning failure [18][19][20][21] . The deterioration in respiratory system mechanics in patients who fail the weaning trial is characterized by an increase in intrinsic positive end-expiratory pressure (PEEP), and inspiratory resistance with a decrease in dynamic lung compliance 22 .…”
Section: Respiratory Pump Failurementioning
confidence: 99%